On σ-subnormal subgroups of finite 3’-groups - Kamornikov, S. F.; Tyutyanov, V. N. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 512.542 For a partition σ of the set R of all primes, it is solved that if every complete Hall set of type σ of a finite 3 ′-group G is reducible in some subgroup H of G, then H is σ -subnormal in G.